Pediatric Burns in the Bedouin Population in Southern Israel - Cohen, Arnon D. (ScientificWorldJournal, 2007)
Burn trauma is an important public health concern, with increased risk for burns in children. A cross-sectional study was performed to describe the epidemiological characteristics and risk factors for burns in hospitalized Bedouin children in Soroka University Medical Center during the years 2001–2002. In a population of 558 hospitalized burn-injured patients, 282 Bedouin children were identified. Two hundred and sixty five patients (94.0%) had burns involving less than 20% of the body surface area. Cause of the burns was scald in 190 patients (67.4%), fire in 80 patients (28.4%), chemical in 8 patients (2.8%), and explosion in 2 patients (0.7%). Two female patients (0.7%) aged 11 and 17 years died of their burns that were caused by fire. The mean length of hospitalization was 9.8 days. Pediatric burn injury has become a significant public health problem in the Bedouin population of the Negev. To reduce the burden of burn injury, it is necessary to increase current efforts in prevention of burns.